The CAP 2013 reform of direct payments: Redistributive effects and impacts on farm income concentration in Italy - Stefano Ciliberti; Angelo Frascarelli (Agricultural and Food Economics, 2018)
The Common Agricultural Policy has traditionally provided support to farm incomes via direct payments under the Single Payment Scheme. This article analyzes whether the reform of the SPS will decrease the concentration of direct payments and evaluates the effect of the new direct payment scheme on the redistribution of farm incomes. The decomposition of the Gini coefficient allows analysis of the evolution of farm income and direct payment distributions in Italy from 2014 to 2020, and empirical results based on the Italian Farm Accountancy Data Network show that the CAP 2013 reform is expected to decrease the concentration of direct payments. However, the reform is also expected to limit the reduction in farm income inequality due to the adoption of a partial convergence model (the so-called 'tunnel' model) instead of a total convergence model as well as, more generally, the increasing share of farm income that is dependent on increased market exposure, leading to higher risks of price volatility and increasing pressure on income.
Keywords: 330; CAP; Gini coefficient; Direct payments; Farm income; FADN; Italy